Functional analysis of ZmG6PE reveals its role in responses to low-phosphorus stress and regulation of grain yield in maize - Zhang, Hongkai; Luo, Bowen; Liu, Jin; Jin, Xinwu; Zhang, Haiying; Zhong, Haixu; Li, Binyang; Hu, Hongmei; Wang, Yikai; Ali, Asif; Riaz, Asad; Sahito, Javed Hussain; et al. (Frontiers in Plant Science, 2023)
A previous metabolomic and genome-wide association analysis of maize screened a glucose-6-phosphate 1-epimerase (ZmG6PE) gene, which responds to low-phosphorus (LP) stress and regulates yield in maize's recombinant inbred lines (RILs). However, the relationship of ZmG6PE with phosphorus and yield remained elusive. This study aimed to elucidate the underlying response mechanism of the ZmG6PE gene to LP stress and its consequential impact on maize yield. The analysis indicated that ZmG6PE required the Aldose_epim conserved domain to maintain enzyme activity and localized in the nucleus and cell membrane. The zmg6pe mutants showed decreased biomass and sugar contents but had increased starch content in leaves under LP stress conditions.Combined transcriptome and metabolome analysis showed that LP stress activated plant immune regulation in response to the LP stress through carbon metabolism, amino acid metabolism, and fatty acid metabolism. Notably, LP stress significantly reduced the synthesis of glucose-1-phosphate, mannose-6-phosphate, and β-alanine-related metabolites and changed the expression of related genes. ZmG6PE regulates LP stress by mediating the expression of ZmSPX6 and ZmPHT1.13. Overall, this study revealed that ZmG6PE affected the number of grains per ear, ear thickness, and ear weight under LP stress, indicating that ZmG6PE participates in the phosphate signaling pathway and affects maize yield-related traits through balancing carbohydrates homeostasis.